2020
DOI: 10.1075/msw.18032.ton
|View full text |Cite
|
Sign up to set email alerts
|

Is a difficult task literally heavy?

Abstract: The conceptualization of abstract concepts is very often metaphorical, meaning that we think and talk about abstract concepts in terms of other, usually more concrete experiences. Recent research suggests that many abstract concepts are linked to bodily sensations. In two experiments, we tested a hypothesis about weight as an embodiment of difficulty. We hypothesized that participants wearing a heavy backpack would judge a psychomotor task to be more difficult than participants wearing an empty backpack. We al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…The actual effort is not required for passing the judgment – a study by Proffitt and colleagues (2003) showed that participants wearing a heavy backpack (but not required to walk with it) judged a distance as long and a hill as steeper than participants with a light backpack. A similar effect was found in a study by Tonković and colleagues (2020) in which participants wearing a heavy backpack judged a psychomotor task more difficult than participants wearing an empty backpack. Durgin and colleagues (2009) argue that these effects are judgmental biases resulting from the social demands of the experimental context.…”
Section: Hypothesessupporting
confidence: 82%
“…The actual effort is not required for passing the judgment – a study by Proffitt and colleagues (2003) showed that participants wearing a heavy backpack (but not required to walk with it) judged a distance as long and a hill as steeper than participants with a light backpack. A similar effect was found in a study by Tonković and colleagues (2020) in which participants wearing a heavy backpack judged a psychomotor task more difficult than participants wearing an empty backpack. Durgin and colleagues (2009) argue that these effects are judgmental biases resulting from the social demands of the experimental context.…”
Section: Hypothesessupporting
confidence: 82%